A Comprehensive Literature Review on Dating Violence Among University Students: Prevention’s Policies and Recommendations for Vietnam - Nguyen, Le Hoai Anh (Journal of Social Policy, Social Change and Development, 2024)
Dating violence (DV) represents a critical public health and safety concern and is global pervasive across diverse populations. It affects individuals irrespective of ethnicity, age, socioeconomic status, occupation, religion, gender, sexual orientation, gender identity, or gender expression. Notably, youths are particularly vulnerable to experiencing dating violence compared to other demographic groups. Additionally, students who identify as lesbian, gay, bisexual, transgender, or queer (LGBTQ), or those uncertain about their gender identity, face higher incidences of physical and sexual dating violence compared to their heterosexual peers. The repercussions of dating violence are profound, encompassing numerous adverse physical and psychological consequences for its victims. Despite the severity of this issue, research on DV, especially regarding prevention policies, remains insufficient in Vietnam. To enhance the well-being of DV victims, comprehensive research on their experiences and the development of effective prevention policies are imperative for Vietnamese universities.